2021
DOI: 10.1101/2021.05.21.445189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of mRNA-1273 against SARS-CoV-2 B.1.351 Infection in Nonhuman Primates

Abstract: Background: Vaccine efficacy against the B.1.351 variant following mRNA-1273 vaccination in humans has not been determined. Nonhuman primates (NHP) are a useful model for demonstrating whether mRNA-1273 mediates protection against B.1.351. Methods: Nonhuman primates received 30 or 100 microgram of mRNA-1273 as a prime-boost vaccine at 0 and 4 weeks, a single immunization of 30 microgram at week 0, or no vaccine. Antibody and T cell responses were assessed in blood, bronchioalveolar lavages (BAL), and nasal was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
(85 reference statements)
0
8
0
Order By: Relevance
“…Initial concerns that SARS-CoV-2 adenovirus or mRNA vaccines would not prevent COVID-19 spread through respiratory droplets or aerosols due to persistence of the virus in nasal swabs and potential for transmission 26 were thwarted by subsequent systematic experiments. [27][28][29][30] Following non-human primate immunization with Moderna mRNA-1273 which encodes the prefusion-stabilized SARS-CoV-2 spike protein encapsulated in a lipid nanoparticle, both circulating and mucosal antibody responses with anti-S IgG binding and neutralizing activity to upper respiratory infections were detected, 29 as well as type 1 helper (Th1) based CD4 T cell responses. 16,31 Correspondingly, in a rodent model, immune responses to Moderna's mRNA-1273 included both antibody and T-cell activation with strong CD4 cytokine responses.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Initial concerns that SARS-CoV-2 adenovirus or mRNA vaccines would not prevent COVID-19 spread through respiratory droplets or aerosols due to persistence of the virus in nasal swabs and potential for transmission 26 were thwarted by subsequent systematic experiments. [27][28][29][30] Following non-human primate immunization with Moderna mRNA-1273 which encodes the prefusion-stabilized SARS-CoV-2 spike protein encapsulated in a lipid nanoparticle, both circulating and mucosal antibody responses with anti-S IgG binding and neutralizing activity to upper respiratory infections were detected, 29 as well as type 1 helper (Th1) based CD4 T cell responses. 16,31 Correspondingly, in a rodent model, immune responses to Moderna's mRNA-1273 included both antibody and T-cell activation with strong CD4 cytokine responses.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…Prechallenge immune profiles predict lung inflammation following SARS-CoV-2 challenge. SARS-CoV-2-specific antibody titers have been implicated in mRNA vaccination-mediated protection from SARS-CoV-2 infection in both humans and NHPs (30,31,33), but the relationship between specific antibody titers and lower respiratory tract inflammation is not clear. To this end, we incorporated previously published data (30) on serum levels of full-length spike protein and receptor-binding domain-specific (RBD-specific) titer IgG present immediately before SARS-CoV-2 challenge in these animals into our analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, the efficacy of these vaccines against severe lower airway disease wanes over time after the initial prime and boost (27)(28)(29). Preclinical and clinical studies have strongly suggested that vaccine-elicited serum levels of SARS-CoV-2-neutralizing antibody titers are a mechanistic immune correlate of vaccine efficacy (30,31). Despite the abundance of clinical and preclinical efficacy data for these mRNA-based vaccine platforms, there is little prospective information currently available on how these vaccines impact SARS-CoV-2-elicited inflammation in the lower respiratory tract with any degree of spatial or temporal resolution.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, some researchers believe that decreased neutralizing activity in vitro does not, on its own, predict that vaccines will be ineffective. Despite the fact that a decline was observed in neutralization response, vaccinees retained a neutralization capability against the Beta variant, possibly due to vaccination stimulating a cross-variant immune response ( Corbett et al, 2021 ; Dejnirattisai et al, 2021 ; Stamatatos et al, 2021 ), as emerging evidence suggests that NAbs might not be the only mechanism of protection. T cells and non-NAbs are considered to also play a vital role in regard to the protection against COVID-19 ( Geers et al, 2021 ; Reynolds et al, 2021 ; Tan et al, 2021 ; Tarke et al, 2021 ).…”
Section: What Factors Influence the Duration Of Protection?mentioning
confidence: 99%